THE SIGNIFICANCE OF DIAGHILEV'S «RUSSIAN SEASONS» IN THE DEVELOPMENT OF CHOREOGRAPHIC ART (Conferencea, 2022)
The article is devoted to the study of the influence of the work and the personality of S. P. Diaghilev. Diaghilev on Russian, European and world culture of the XX-XXI centuries. The activity of S. P. Diaghilev and the World Art Workers is analyzed. The article analyzes the activity of S. P. Diaghilev and people of Myrish art, who were in the vanguard of creative quests of their time, advocated renewal of Russian culture, formed a new approach to the phenomenon of the Artist in the key aspects of his "self-identification" and comprehension of the purpose of art - to be "art for art" or "art for life". This culture can be useful in the 21st century, forming a holistic worldview that overcomes fragmentation, fragmentation and cliches. С. P. Diaghilev was the creator of a new era in the art of the first third of the twentieth century. "Diaghilev's Russian Seasons (Les Saisons Russes, since 1906), then the Russian Ballets (Les Ballets Russes, since 1911) became the center of gravity of diverse artistic interests, a laboratory of a consistent search for forms and methods in various fields of art, daring ideas and projects, united in a modernist synthesis, and had a significant impact on the art of the twentieth century